Developing quality measures for adolescent care: validity of adolescents' self-reported receipt of preventive services. - Klein, J D (1999)
OBJECTIVE: To demonstrate the feasibility of directly surveying adolescents about the content of preventive health services they have received and to assess the validity of adolescent self-reported recall. DATA SOURCES/SETTING: Audiotaped encounters, telephone interviews, and chart reviews with 14-21 year olds being seen for preventive care visits at 15 pediatric and family medicine private practices, teaching hospital clinics, and health centers. DESIGN: 537 adolescents presenting for well visits were approached, 400 (75 percent) consented, 374 (94 percent) were audiotaped, and 354 (89 percent) completed telephone interviews either two to four weeks or five to seven months after their visits. Audiotapes were coded for screening and counseling across 34 preventive service content areas. Intraobserver reliability (Cohen's kappa) ranged from 0.45 for talking about peers to 0.94 for discussing tobacco. The sensitivity and specificity of the adolescent self-reports were assessed using the audiotape coding as the gold standard. RESULTS: Almost all adolescents surveyed (94 percent) remembered having had a preventive care visit, 93 percent identified the site of care, and most (84 percent) identified the clinician they had seen. There was wide variation in the prevalence of screening, based on the tape coding. Adolescent self-report was moderately or highly sensitive and specific at two weeks and six months for 24 of 34 screening and counseling items, including having discussed: weight, diet, body image, exercise, seatbelts, bike helmet use, cigarettes/smoking, smokeless tobacco, alcohol, drugs, steroids, sex, sexual orientation, birth control, condoms, HIV, STDs, school, family, future plans, emotions, suicidality, and abuse. Self-report was least accurate for blood pressure/cholesterol screening, immunizations, or for having discussed fighting, violence, weapon carrying, sleep, dental care, friends, or over-the-counter drug use. CONCLUSION: Adolescents' self-report of the care they have received is a valid method of determining the content of preventive health service delivery. Although recall of screening and counseling is more accurate within two to four weeks after preventive care visits, adolescents can report accurately on the care they had received five to seven months after the preventive health care visits occurred.